TOTAL QUALITY MANAGEMENT: DO THEY IMPROVES INSTITUTIONS PERFORMANCE AND PERFORMANCE EFFICIENCY - Iqbal Kumail Awad; Sami Abdullah Kadhim (Scholars Digest Publishing, 2025)
With the increasing phenomenon of problems in educational institutions, Total Quality Management (TQM) has become an important subject in its educational scope practice. However, the focus of universities in the implementation of TQM is to increase they improve Institutions Performance (IP) and Performance Efficiency (PE). The aim of this research is to review the literature on TQM and its relationship toward institutions performance and performance efficiency. This paper analyses the link between TQM and institutions performance and performance efficiency.
Keywords: Total Quality Management (TQM), Institutions Performance, Performance Efficiency.